2019
DOI: 10.15407/ukrbotj75.06.564
|View full text |Cite
|
Sign up to set email alerts
|

DNA extraction from old herbarium material of Veronica subgen. Pseudolysimachium (Plantaginaceae)

Abstract: Herbarium specimens have become a major source of information in molecular biodiversity research, framing the term "herbarium genomics". However, obtaining good DNA from old herbarium specimens is still a challenge. Currently, DNA extraction methods from old herbarium material often yield highly degraded and fragmented DNA. A number of studies have discussed such methods, especially how to avoid further DNA fragmentation. This study aims to compare different DNA extraction methods applied to old herbarium mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 33 publications
0
13
4
Order By: Relevance
“…Older samples had in general lower yield, especially when using the commercial extraction kit. Our results contrast those of other studies (19,39), where no correlation was found between age of the specimens and DNA yield. The reason of this discrepancy might be explained by sampling peculiarities.…”
Section: Effect Of Specimens' Age On Yield and Qualitycontrasting
confidence: 99%
See 2 more Smart Citations
“…Older samples had in general lower yield, especially when using the commercial extraction kit. Our results contrast those of other studies (19,39), where no correlation was found between age of the specimens and DNA yield. The reason of this discrepancy might be explained by sampling peculiarities.…”
Section: Effect Of Specimens' Age On Yield and Qualitycontrasting
confidence: 99%
“…The first studies on ancient or archival DNA (aDNA) from plants were published in the early 90s of the last century and dealt with plant remains in archaeological sites (e.g., (15,16) among others). Studies dealing with DNA extraction from old herbarium samples have used one of the following approaches: i) Early studies on herbarium material aiming at sequencing single markers, e.g., ITS, simply used standard CTAB protocols for extraction (17) or a modified version of it (12,(18)(19)(20)(21); ii) commercial kits were used with few adaptations, e.g., increasing incubation times (18,19,22,23); or, iii) more specific protocols for aDNA extraction were applied (e.g., optimized to obtain short sequences and to increase the proportion of endogenous DNA in the extracts; (10,12,13,24). Since then, more and more studies included historical plant material in phylogenomic studies (7,23,25,26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extra modifications (recommended when polysaccharides and secondary metabolites are abundant) include sorbitol and high‐salt (4 M NaCl) CTAB (e.g., for mucilage‐rich tissue, Tel‐Zur et al., ; Štorchová et al., ) or 2% polyvinylpyrrolidone (PVP) (e.g., for latex‐rich tissue, Michiels et al., ). When phenol use is restricted (e.g., in light of health and safety concerns), additional clean‐up steps are recommended, such as column (e.g., CsCl‐EtBr density gradient centrifugation, Albach and Chase, ; Ahmed et al., ; Höpke et al., ) or bead cleaning (e.g., solid‐phase reversible immobilization [e.g., SPRIselect beads, Beckman Coulter, Indianapolis, Indiana, USA]; Shee et al., ), and even additional modified CTAB protocols optimized for plant lineages with high levels of polysaccharides and secondary metabolites (Štorchová et al., ; Sahu et al., ).…”
Section: Dna Extractionmentioning
confidence: 99%
“…In recent years, assessing techniques of DNA isolation and sequencing from herbarium plant material has gained broad interest (e.g. Rogers & Bendich, 1985;Goff & Moon, 1993;Savolainen et al, 1995;Porebski, Bailey & Baum, 1997;Blattner, 1999;Drábková, Kirschner & Vlĉek, 2002;DeCastro & Menale, 2004;Jankowiak, Buczkowska & Szweykowska-Kulinska, 2005;Cota-Sánchez, Remarchuk & Ubayasena, 2006;Telle & Thines, 2008;Soni & Kumar, 2009;Lehtonen & Christenhusz, 2010;Staats et al, 2011;Särkinen et al, 2012;Staats et al, 2013;Shepherd & Perrie, 2014;Shepherd, 2017;Do & Drábková, 2018;Höpke et al, 2019). The primary aim of such technical investigations is to establish appropriate methods of efficient DNA analysis from preserved plant specimens, taking into account the specificity of such source material.…”
Section: Introductionmentioning
confidence: 99%